2014
DOI: 10.1016/j.neuroimage.2014.04.082
|View full text |Cite
|
Sign up to set email alerts
|

Cortical activation to object shape and speed of motion during the first year

Abstract: A great deal is known about the functional organization of cortical networks that mediate visual object processing in the adult. The current research is part of a growing effort to identify the functional maturation of these pathways in the developing brain. The current research used near-infrared spectroscopy to investigate functional activation of the infant cortex during the processing of featural information (shape) and spatiotemporal information (speed of motion) during the first year of life. Our investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
48
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(51 citation statements)
references
References 74 publications
2
48
1
Order By: Relevance
“…fNIRS studies have revealed that activation is obtained in the anterior temporal cortex to events in which spatiotemporal discontinuities (e.g., discontinuities in path or speed of motion) signal the presence of distinct objects. Control events (like that in Figure 2A) do not elicit activation in the anterior temporal cortex [49, 51]. This confirms and extends the individuation-by-feature results by revealing that the anterior temporal cortex is activated regardless of how the objects were individuated (e.g., on the basis of featural or spatiotemporal information).…”
Section: Object Processing In the Infant Brainsupporting
confidence: 72%
See 3 more Smart Citations
“…fNIRS studies have revealed that activation is obtained in the anterior temporal cortex to events in which spatiotemporal discontinuities (e.g., discontinuities in path or speed of motion) signal the presence of distinct objects. Control events (like that in Figure 2A) do not elicit activation in the anterior temporal cortex [49, 51]. This confirms and extends the individuation-by-feature results by revealing that the anterior temporal cortex is activated regardless of how the objects were individuated (e.g., on the basis of featural or spatiotemporal information).…”
Section: Object Processing In the Infant Brainsupporting
confidence: 72%
“…However, posterior temporal responses change markedly during the first year. Regardless of event condition, by 7 months activation in posterior temporal areas wane, and by 12 months is no longer observed for this task [50,51]. These results suggest a functional reorganization of the ventral object-processing network during the second half of the first year.…”
Section: Object Processing In the Infant Brainmentioning
confidence: 99%
See 2 more Smart Citations
“…There is considerable interest in using functional near-infared spectroscopy (fNIRS) to study infants with more recent studies (since July 2012) covering its broad potential as a noninvasive tool to study infant cognition, 10 typical and atypical development, 11 and, more specifically, to study face recognition, [12][13][14] shape processing, and motion 15,16 and color priming. 17 Despite the rapid growth in the number of infant fNIRS publications in recent years, this number is relatively low when compared to that of adult studies.…”
Section: Introductionmentioning
confidence: 99%